Safety Culture is an Important Argument to Reduce Individual, Social and Global Risks - Rasulev , A. X.; O. Zh., Mukharramov; Urmanov, I. R. (European Journal of Life Safety and Stability (2660-9630), 2022)
At present formed understanding that that culture to safety must be applicable not only to personnel potentially dangerous object, but also to each person separately, society as a whole. From value of the installing the people, the motive of their behaviour, larval and professional quality and abilities depends in defining degree efficiency action on provision of safety to vital activity, reduction individual, social and global risk.